Pemberdayaan Masyarakat melalui Budidaya dan Pengolahan Sayuran Microgreen di Desa Cisaat, Kecamatan Ciater, Kabupaten Subang - Pasaribu, Pinta Omas; Indrayanti, Reni; Adisyahputra, Adisyahputra; Asharo, Rizal Koen; Rizkawati, Vina; Achmad, Farhana Faridah; Febrian, Reyno Ahmad; Utari, Raysita (Jurnal SOLMA, 2025)
Background: Cisaat Village, located in Ciater District, Subang Regency, has significant agricultural potential. Most of its residents rely on agriculture as their primary source of livelihood. However, efforts to diversify agriculture and optimize land use in Cisaat Village have not been fully maximized. Most farmers still depend on conventional farming systems, which face challenges such as seasonal dependency, high production costs, and limited access to more efficient agricultural innovations. The purpose of comminity is introduce the public to the cultivation and processing of microgreens as a food source to boost the household economics in Cisaat Village, Ciater District, Subang Regency. Methods: The community service activity was carried out through socialization in the form of lectures, discussions, and demonstrations or hands-on practice on microgreen cultivation techniques and benefits. The evaluation was conducted using a pre-test before the activity and a post-test afterward to measure participants' improvement in understanding. The pre-test and post-test data were statistically analyzed using the Dependent T-test to determine the significance of differences before and after the activity. Results: Participants demonstrated high enthusiasm and were actively engaged throughout the activity. The T-test results showed a significant improvement in understanding, with the average pre-test score of 46.44 increasing sharply to 86.04 in the post-test (p < 0.05). This indicates that the applied method has proven to be effective. Conclusions: This socialization, combined with live demonstrations, proved helpful in introducing participants and boosting their interest in growing microgreens, both to meet household vegetable needs and as an additional income opportunity.